Extracellular fraction of adipose tissue as an innovative regenerative approach for vitiligo treatment. Issue 6 (19th June 2019) - Bellei, Barbara; Papaccio, Federica; Filoni, Angela; Caputo, Silvia; Lopez, Gianluca; Migliano, Emilia; Picardo, Mauro
Abstract: Vitiligo is a common, disfiguring autoimmune disease that negatively affects patients' self‐esteem and quality of life. Current treatments are moderately effective in reversing disease and promoting melanocyte regeneration. Thus, therapeutic advanced strategies are emerging from regenerative medicine. It has recently emerged that adipose tissue secretome may be used as a cell‐free therapy in skin regeneration since paracrine functions of adipose‐derived stem cells alone are responsible for most of the therapeutic effect of stem cells in several animal disease models. In this study, we tested the effect of adipose tissue extracellular fraction (AT‐Ex) isolated from lipoaspirates on dermal and epidermal vitiligo cells in vitro. Using this experimental model, we demonstrated that molecules secreted by adipose tissue ameliorate the capability to counteract oxidative stress by a physiological stimulation of intracellular antioxidant enzymes and positively impact on cell proliferation. Due to the presence of Wnt‐secreted factors, AT‐Ex treatment promotes glycogen synthase kinase 3β inactivation and consequently Wnt/β‐catenin pathway activation. Collectively, our findings show that AT‐Ex could be useful as a natural approach to improve treatment of vitiligo.